Nepostavené Brno - Bureš, David (Vysoké učení technické v Brně, Fakulta architektury, 2011)
V článku je stručně charakterizováno meziválečné období v Brně. Jsou zde shrnuty nejdůležitější kulturní, sociální a ekonomické souvislosti. Představeny budou vybrané zajímavé nebo významné projekty v oblasti dopravy, školství a kultury.

The topic is Unbuilt Brno. The subject is unrealized or partially complete architectural and urban projects that were designed for the city Brno and in particular from the interwarperiod. In the interest will be areas in contact with the urban core, for which it is currentlylooking for suitable use (for example South Centre, Academy Square, ...). In addition, areas where a project was started, but for various reasons was not completedand now we thought it escapes (např. Kraví hora, Peace Square). Attention will also focus on the site, who lost his position, but a unique place and can offer huge potential (např. Ponava).
Unbulit Brno
Keywords: meziválečné Brno, regulace dopravy, Akademické náměstí, Kraví hora, divadla